Lumbosacral tuft of hair as a key stigma for early detection of occult spinal dysraphism: A case report of diastematomyelia with tethered cord in a newborn - Roya Farhadi; Seyed Amir Kazemi; Farnaz Godazandeh (Clinical Case Reports)
Key Clinical Message Early detection of occult spinal dysraphism, such as diastematomyelia with tethered cord, is vital to prevent neurological damage. Though rarely diagnosed in the neonatal period, cutaneous stigmata can aid early identification. Utilizing neonatal ultrasound enables timely management and multidisciplinary intervention.